The Influence of Sports Brand English Translation and Publicity on the Psychology of Mass Sports Exercise - Bo Ning, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The English language, similar to all languages, serves as a vessel for conveying the cultural nuances of English-speaking nations. Notably, sports, being a significant component of culture, naturally infiltrates the language. A considerable number of words, phrases, and expressions within the English language find their roots in various sports, thus substantially enhancing the lexicon of the language. Leveraging translated sports media for enhancing the overall quality of sports engagement among college students is aimed at nurturing accurate sports principles and a perpetual sports awareness. This endeavour has emerged as a pivotal facet within the domain of social science and sports research innovation. In the context of the psychological characteristics inherent in provincial college students, a comprehensive research methodology is employed to scrutinize and assess the present state of college students' interaction with sports media, alongside the factors shaping the sporting values embraced by college students in the region. Drawing upon the results of a conducted survey, the primary motives behind college students' admiration for sports celebrities include the capacity to idolize sports stars (43.66%), appreciation for the athletic prowess displayed by these luminaries (40.12%), respect for sports figures (34.63%), recognition of their professional attributes, and other qualities they embody (25.87%). Notably, a considerable portion of those who hold sports stars in high esteem also exhibit elevated economic means (12.91%). The authors explored and examined the college students' exposure to translated sports media content, along with the media's influence on their sports-related values, active involvement in sports, and extracurricular pursuits, impart valuable theoretical insights pertinent to the progression of collegiate sports, the effective utilization of mass media, the provision of Olympic brand education for college students, and the reform of higher education sports programs. For the inaugural instance, we have gleaned that the sources employed for procuring Olympic tickets have started to shift. Internet-based platforms constitute over 40% of these sources, with television channels accounting for a similar proportion, hovering around 40%. In contrast, traditional print media, such as newspapers and magazines, comprises a mere 6.5%, while radio media falls below 3%. Approximately 21.6% of adolescents hold sports stars in high esteem, and 41.7% of them believe that the adoration of "sports stars" contributes to their personal development, while 33.3% of adolescents endeavour to attend events featuring their favourite celebrities. In accordance with the pertinent survey, more than half of college students profess to idolization, of which one-quarter revere sports stars. Currently, the impact of the translation and promotion of sports brand media on the sports values of college students is predominantly positive, characterized by a "favourable disposition." A strong and positive correlation exists between sports brand media and the values held by college students. Sociolinguists have emphasized that sports constitutes a pivotal component of culture, and culture and language form an inseparable and integrated entity. Language functions as the conduit for transmitting culture, and sports continuously contribute to the enhancement and enrichment of language. The commercialization of sports, combined with extensive media coverage, has spurred an unprecedented surge in the public's affection for sports. Consequently, various sports events have ingrained themselves deeply in the hearts of people, and the sports-related terminology used by individuals across a spectrum of athletic activities, contests, and competitions has evolved into a distinctive hallmark within the English language.